2019
DOI: 10.3390/medicina55100642
|View full text |Cite
|
Sign up to set email alerts
|

IL28B Genetic Variations in Patients with Recurrent Herpes Simplex Keratitis

Abstract: Background and objectives: Recurrent herpes simplex keratitis (HSK) is the most common cause of corneal blindness in the developed world. A relationship between host gene polymorphisms and the recurrence of herpes simplex virus (HSV) infection has previously been proposed. Thus, the aim of this study was to investigate a potential association between the IL28B host genotype and recurrent HSK. Materials and Methods: Eighty patients older than 18 years of age of both genders with a history of recurrent herpes si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 33 publications
0
1
0
Order By: Relevance
“…Danileviciene et al [ 154 ], identified the role of the C21orf91 gene in the development of HSK where they described the condition to be 2.9 times more likely in patients with the rs10446073 genotype being more common[ 154 ]. According to Borivoje et al [ 155 ], the CC IL28B gene has been identified to be present in individuals with recurrent HSK[ 155 ].…”
Section: Diagnostic Approaches For Herpes Simplex Keratitis: Challeng...mentioning
confidence: 99%
“…Danileviciene et al [ 154 ], identified the role of the C21orf91 gene in the development of HSK where they described the condition to be 2.9 times more likely in patients with the rs10446073 genotype being more common[ 154 ]. According to Borivoje et al [ 155 ], the CC IL28B gene has been identified to be present in individuals with recurrent HSK[ 155 ].…”
Section: Diagnostic Approaches For Herpes Simplex Keratitis: Challeng...mentioning
confidence: 99%
“…Resistance to Pseudomonas aeruginosa infection was higher in miR-183/96/182 cluster knockdown mice compared to wild-type mice [11,12] and the upregulation of miR-155 was reported to increase corneal susceptibility to P. aeruginosa [13]. Furthermore, a relationship between recurrent herpes simplex keratitis and host gene polymorphisms has been proposed [14].…”
Section: Introductionmentioning
confidence: 99%